Himalayan bridge
1 online resource
Keywords: The centrality of the Himalayas as a connecting point or perhaps a sacred core for the Asian continent and its civilisations has captivated every explorer and scholar. The Himalaya is the meeting point of two geotectonic plates, three biogeographical realms, two ancient civilisations, two different language streams and six religions.This book is about the determinant factors which are at work in the Himalayas in the context of what it constitutes in terms of its spatiality, legends and myths, religious beliefs, rituals and traditions. The book suggests that there is no single way for understanding the Himalayas. There are layers of structures, imposition and superimposition of human history, religious traits and beliefs that continue to shape the Asian dynamics. An understanding of the ultimate union of the Himalayas, its confluences and its bridging role is essential for Asian balance. This book is a collaborative effort of an internationally acclaimed linguist, a diplomat-cum-geopolitician and a young Asianist. It provides countless themes that will be intellectually stimulating to scholars and students with varied interests. Please note: This title is co-published with KW Publishers, New Delhi. Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.